2020
DOI: 10.1111/jne.12900
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of fatty acids on autophagy in NPY neurones

Abstract: High-fat diet (HFD) feeding is deleterious to hypothalamic tissue, leading to inflammation and lipotoxicity, as well as contributing to central insulin resistance. Autophagy is a process that restores cellular homeostasis by degrading malfunctioning organelles and proteins. Chronic HFD-feeding down-regulates hypothalamic autophagy. However, the effects of short-term HFD-feeding and the saturated fatty acid palmitate (PA) on hypothalamic autophagy and in neurones that express neuropeptide Y (NPY) and agouti-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 74 publications
(206 reference statements)
0
15
0
Order By: Relevance
“…The protective effects of DGAT1 in mice with cardiomyopathy [ 114 116 ] suggest that it is more advantageous to store fatty acids in LDs in the form of triglycerides and gradually release these fatty acids through lipolysis or lipophagy than to convert these fatty acids into toxic lipids. In addition, various fatty acids can modulate the rate of autophagic activity [ 117 ], but whether this involves lipophagy remains to be confirmed. As a key function of autophagy, continuous cell quality control ensures that damaged organelles [ 118 ], lipids, and proteins can regulate turnover.…”
Section: Regulation and Function Of Lipophagymentioning
confidence: 99%
“…The protective effects of DGAT1 in mice with cardiomyopathy [ 114 116 ] suggest that it is more advantageous to store fatty acids in LDs in the form of triglycerides and gradually release these fatty acids through lipolysis or lipophagy than to convert these fatty acids into toxic lipids. In addition, various fatty acids can modulate the rate of autophagic activity [ 117 ], but whether this involves lipophagy remains to be confirmed. As a key function of autophagy, continuous cell quality control ensures that damaged organelles [ 118 ], lipids, and proteins can regulate turnover.…”
Section: Regulation and Function Of Lipophagymentioning
confidence: 99%
“…However, the role of FFAs in the hypothalamus during fasting, beyond regulation of neuropeptide expression, has not been well elucidated. Given the starvationinduced ER stress [32] and autophagy [31,[33][34][35] in hypothalamic cells, circulating palmitate under fasting might regulate ER stress and ER-phagy, affecting hypothalamic functions.…”
Section: Introductionmentioning
confidence: 99%
“…In NPY/AgRP hypothalamic neurons, autophagy-regulated lipid metabolism has been shown to modulate neuropeptide levels which have immediate effects on food intake [ 63 ]. Interestingly, Milanski and colleagues recently showed that palmitate-mediated induction of autophagy in the NPY-expressing neuronal cell model mHypoE-46 is dependent on de novo ceramide biosynthesis [ 64 ]. These results suggest that increased de novo ceramide biosynthesis in different neuronal populations is involved in the regulation of energy homeostasis.…”
Section: Does De Novo Ceramide Biosynthesis Play a Role In Hypothalamic Lipotoxicity-induced Obesity?mentioning
confidence: 99%